Morphology and epicuticular wax content of coffee leaves after fungicide application - Lichston, Juliana Espada; Godoy, Silvana Aparecida Pires de (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effect of fungicide application on the content and morphology of the epicuticular wax of two Coffea arabica L. cultivars, one rust resistant (Obatã) and other susceptible (Catuaí Vermelho). Plants were grouped according to treatment (with and without fungicide application), sampling the leaves from 5th and 6th nodes, one for morphology study and two others for wax content. The fungicide application decreased wax content and modified its morphology, causing ruptures and missing crystalloids that can make the plant more susceptible to diseases, herbivory and desiccation. Cultivars differ in their content and morphology wax, which can be related to the rust resistance observed in the Obatã cultivar.